Pengaruh Kepuasan Wajib Pajak terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Natasya, Erika; Andhaniwati, Erry (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Tax is a sector that has a major influence on state revenues. Taxes are used as a source of state income which is then used to finance state expenditures. Taxpayer compliance in paying taxes is very important as a source of income for the Indonesian state in order to design national development, both in terms of economic, political, taxation and legal development. The purpose of this research is to find out and prove the effect of taxpayer satisfaction on motor vehicle tax compliance. The theory used in this research is Theory of Planned Behavior. This research was conducted using primary data using quantitative methods through questionnaires and random sampling data collection techniques with a sample of 100 motorized vehicle taxpayers in the Gresik District SAMSAT. In testing the researcher uses partial least squares analysis and is processed through tests carried out on SmartPLS 4.0 software. The results showed that taxpayer satisfaction had an effect on motor vehicle tax compliance. This research has implications for tax agencies to continue to develop innovation and increase taxpayer satisfaction. Keywords: Taxpayer compliance, Taxpayer satisfaction.